1995
DOI: 10.1111/j.1540-4781.1995.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grammar Supplementation on Written Accuracy in an Intermediate Spanish Content Course

Abstract: Two sections of an intermediate Spanish content course were supplemented with grammar (daily grammar review and error correction feedback on written work); two comparison group sections lacked the grammar component. Two written pre‐/posttests—one grammar‐focused, one integrative (an essay)—showed that both groups exhibited significant improvement over the semester in overall grammatical accuracy on both instruments. The plus‐grammar group significantly outperformed the nongrammar group on the grammar‐focused i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(24 citation statements)
references
References 35 publications
1
21
1
1
Order By: Relevance
“…Most English as a second language (ESL) and foreign language writing practitioners agree on one basic point in relation to writing in a nonnative language: Writing in and of itself increases language competency and proficiency regardless of the subsequent treatment later received (Chandler, 2003;Fathman & Whalley, 1990;Frantzen, 1995;Polio, Fleck, & Leder, 1998;Robb, Ross, & Shortreed, 1986;Semke, 1982). Researchers claim that the more students write, the more their ability to write fluently and accurately improves (Frantzen, 1995;Robb et al, 1986).…”
Section: Amount and Location Of Composingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most English as a second language (ESL) and foreign language writing practitioners agree on one basic point in relation to writing in a nonnative language: Writing in and of itself increases language competency and proficiency regardless of the subsequent treatment later received (Chandler, 2003;Fathman & Whalley, 1990;Frantzen, 1995;Polio, Fleck, & Leder, 1998;Robb, Ross, & Shortreed, 1986;Semke, 1982). Researchers claim that the more students write, the more their ability to write fluently and accurately improves (Frantzen, 1995;Robb et al, 1986).…”
Section: Amount and Location Of Composingmentioning
confidence: 99%
“…Most English as a second language (ESL) and foreign language writing practitioners agree on one basic point in relation to writing in a nonnative language: Writing in and of itself increases language competency and proficiency regardless of the subsequent treatment later received (Chandler, 2003;Fathman & Whalley, 1990;Frantzen, 1995;Polio, Fleck, & Leder, 1998;Robb, Ross, & Shortreed, 1986;Semke, 1982). Researchers claim that the more students write, the more their ability to write fluently and accurately improves (Frantzen, 1995;Robb et al, 1986). There is some discussion, however, concerning which types of writing are most beneficial to foreign language learners at different stages of language development: Reichelt (1999) suggests that one area in which more foreign language research is necessary is the development of a needs analysis to determine what students are expected to do as foreign language writers beyond the language classroom, so that once expectations are determined, instruction can be tailored to students' future needs.…”
Section: Amount and Location Of Composingmentioning
confidence: 99%
“…There were no significant differences on these 3 measures. Frantzen (1995) examined the effects of supplemental grammar instruction on grammatical accuracy in the compositions of U.S. university Spanish students. To measure grammatical accuracy, Frantzen used 12 categories and scored essays for the correct use of a particular structure divided by the total number of obligatory contexts for that structure.…”
Section: Error Count With Classificationmentioning
confidence: 99%
“…Robb, Ross, and Shortreed (1986) examined the effect of different methods of feedback on essays. More recently, Ishikawa (1995) looked at different teaching techniques and Frantzen (1995) studied the effect of supplemental grammar work.…”
mentioning
confidence: 99%
“…Because many studies have focused on novice-or intermediate-level students, articles on the teaching of writing in FL classes have tended to focus primarily on improving linguistic accuracy rather than improving the organization of ideas and strength of content. For example, Hsu (2014), Polio (2012), Frantzen (1995), Manley and Calk (1997), Cooper and Morain (1980), and Cooper (1981) primarily investigated the effects of writing instruction on grammatical accuracy in FL contexts, as did Truscott (1996Truscott ( , 1999, Ferris (1999Ferris ( , 2002Ferris ( , 2009), Bitchener (2008), Longcope (2009), and Bitchener and Ferris (2012) in EFL or ESL contexts. In a study involving 21 intermediate-level students of French, New (1994) found that students rarely revised papers for content; rather, their revisions focused on form, such as verb conjugations, spellings, and word choice.…”
Section: Literature Review Foreign Language/second Language Writing Vmentioning
confidence: 99%